2017
DOI: 10.1016/j.heares.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of noise-induced hearing loss

Abstract: Exposure to intense sound or noise can result in purely temporary threshold shift (TTS), or leave a residual permanent threshold shift (PTS) along with alterations in growth functions of auditory nerve output. Recent research has revealed a number of mechanisms that contribute to noise-induced hearing loss (NIHL). The principle cause of NIHL is damage to cochlear hair cells and associated synaptopathy. Contributions to TTS include reversible damage to hair cell (HC) stereocilia or synapses, while moderate TTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
228
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(240 citation statements)
references
References 120 publications
2
228
1
9
Order By: Relevance
“…Hearing loss is a serious global morbidity that affects 360 million people worldwide [1], and this neurological disability impacts both the physical and mental health of patients [2]. Recent research has revealed several mechanisms and molecules that contribute to hearing loss, such as oxidative stress and apoptotic cell death [3]. Oxidative stress plays a critical role in the pathogenesis of hearing loss and in diabetes-related and environmental/occupational exposure-associated complications [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing loss is a serious global morbidity that affects 360 million people worldwide [1], and this neurological disability impacts both the physical and mental health of patients [2]. Recent research has revealed several mechanisms and molecules that contribute to hearing loss, such as oxidative stress and apoptotic cell death [3]. Oxidative stress plays a critical role in the pathogenesis of hearing loss and in diabetes-related and environmental/occupational exposure-associated complications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence suggests that excessive oxidative stress in the cochlea is closely related to the pathogenesis of hearing loss [3,6]. Therefore, pharmacologically reducing oxidative stress and strengthening the cochlear resistance against oxidative stress and cytotoxic chemicals are effective prevention strategies for maintaining the structural and functional integrity of the cochlea to prevent the development and progression of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…10 The mechanism of damage includes accretion of the reactive oxygen genus and stimulation of the intracellular stress pathway, that leads to cell death. 11 Hearing loss due to cochlear dysfunction also changes the organization of the central auditory pathway. 12 Varying degrees of permanent deafness occurs due to damage to inner ear.…”
Section: Original Articlementioning
confidence: 99%
“…Finally, from the metabolic perspective, using 18 F‐fluro‐deoxy‐glucose (FDG) positron Emission Tomography (PET), Verger et al () have revealed a specific pattern of decreased regional cerebral blood flow (CBF), a quantitative measure of baseline neuronal metabolism, in the associative auditory cortex of HL patients (mainly in the right hemisphere). While HL is frequently caused by accumulated noise and ototoxic experiences that produce a loss of sensory cells in the cochlea (Kurabi, Keithley, Housley, Ryan, & Wong, ), a possible reduction in the regional CBF in the auditory cortex may also indicate the presence of a vascular dysfunction, which could lead itself to neuronal deficits. In fact, because CBF is regulated according to local neuronal activity and metabolism (i.e., neurovascular coupling; Iadecola, ), if CBF deficiency is prior to neurodegeneration, a reduced CBF in the central auditory system of HL patients could be linked to a reduced dilatory capacity of cerebral vasculature in upregulating perfusion, with an increased risk for vascular disease and a higher vulnerability for neurological disorders in aging (Gao et al, ).…”
Section: Introductionmentioning
confidence: 99%